Antibiotic prophilaxis in head and neck surgery: 24 or 72 hours? - Ramos, Gyl Henrique Albrecht (2002)
Objectives: the antibiotic prophylaxis in oncologic head and neck surgery is a complex issue. Despite of literature reports do not show significant differences in the occurrence of wound infection, before changing the time of prophylaxis of 72 hours to 24 hours, a prospective and randomized trial was set up. The trial was conducted in the Erasto Gaertner Hospital - Head and Neck Surgery Department. Methods: from December,1993 to August,1998, 93 patients submitted to total laryngectomy and pelviglossomandibulectomy were included in the protocol, with detailed information about the antibiotic prophylaxis time and the existence of wound infection. Results: the 24 hour group (39 cases) had a 10% infection rate, and the 72 hours group had a 22% infection rate. Conclusion: there was no significant differences in the infection rate between the groups. A similar trial has been conducted comparing 8 hours versus 24 hours of antibiotic prophylaxis.